Philippines Quarterly Update, March 2012 : From Stability to Prosperity for All - World Bank (World Bank, Manila, 2017)
The Philippine economy grew slower than expected at 3.7 percent in 2011, held back by weak public spending and external demand. In the fourth quarter (Q4), growth slightly improved at 3.7 percent. As in past quarters, growth was driven by remittance-fueled household consumption, which grew by 6.7 percent. The government's disbursement acceleration plan was partially successful and contributed 1.3 percentage points (ppt) to gross domestic product, or GDP growth in Q4, up from 0.3 ppt in Q3, but this was not enough to push growth up to the targeted level of around five percent. On the production side, the services sector, including the fast-growing business process outsourcing (BPO) industry, continued to drive growth. Industry, in particular exports manufacturing, was buffeted by weaker demand, while agriculture suffered from typhoon damages, highlighting the need to improve disaster and risk management. The country is benefiting from strong macroeconomic fundamentals, political stability, and a popular government that is seen by many as committed to improving governance and reducing poverty. Several reforms have successfully started, notably in public financial management. However, the window of opportunity is narrowing given elections in 2013 and 2016 and the historical difficulty of moving forward with reforms when the campaign period kicks in. Now is the time to implement the reforms needs to accelerate growth, create jobs, and reduce poverty.